PENGEMBANGAN STRATEGI MANAJEMEN UKM HOMESTAY DI KECAMATAN NUSALAUT, MALUKU TENGAH - Abdulharis Tamalene; Kalsum Lussy; Marsya S.I. Matitaputty (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to analyse the weaknesses of management strategies and identify local tourism potential for the development of homestay SMEs in Nusalaut District, Central Maluku. Method: This research uses a qualitative approach, focusing on four villages with homestay accommodations. Results: The results show that the growth of the homestay business in Nusalaut is hindered by minimal promotion, a lack of local service competencies, and, most critically, the absence of formal Standard Operating Procedures (SOPs) and the yet-to-be-established Tourism Awareness Group (Pokdarwis). The proposed management strategy emphasises service standardisation through local wisdom-based SOPs, enhancing human resource capacity through training, and the formation of Pokdarwis as coordinators for integrated tourism promotion. Implementing this strategy is important to encourage sustainable community-based tourism (CBT) in Nusalaut. Keywords: Community-Based Tourism, Homestay SMEs, Management Strategy, Pokdarwis, Nusalaut.